A spatial and temporal assessment of fire regimes on different vegetation types using MODIS burnt area products - Buthelezi, Nokuphila L.P.; Mutanga, Onisimo; Rouget, Mathieu; Sibanda, Mbulisi (African Biodiversity & Conservation, 2016)
Background: The role of fire in maintaining grassland diversity has been widely recognised; however, its effect in KwaZulu-Natal grasslands is still rudimentary. In that regard, understanding fire regimes of different vegetation types in KwaZulu-Natal is a critical step towards the development of effective management strategies that are specific to each vegetation type. Objective: To assess the effect of different vegetation types on fire regimes in KwaZulu-Natal using moderate resolution imaging spectroradiometer (MODIS) burnt fire products. Method: Ten years of fire data for four different vegetation types (Ngongoni Veld, KwaZulu-Natal Sandstone Sourveld, Eastern Valley Bushveld and KwaZulu-Natal Coastal Belt) were extracted from the MODIS products and used as a basis to establish three parameters: annual burnt areas, fire season and fire frequency. The total burnt area within each vegetation type over the 10-year period was quantified. Results: The KZN Sandstone Sourveld had a high-burnt area of 80% in 2009 with KwaZulu-Natal Coastal Belt having the least burnt area of less than 5%. Ngongoni Veld and the KwaZulu-Natal Sandstone Sourveld had the highest fire frequency, while the coastal region had low fire frequencies. Results showed high fire prevalence during the late period of the dry season (which extends from June to August) across all the vegetation types. Conclusion: This study underscores the potential of remotely sensed data (MODIS burned area products) in providing a comprehensive view of fire patterns in different vegetation types.